Wound Healing Potential of Crocin and Safranal, Main Saffron (Crocus sativus L.), the Active Constituents in Excision Wound Model in Rats: - Heydari, Mojtaba; Deldar, Nafise; Monsefi, Malihezaman; Salmanpour, Mohsen; Ostovar, Mohadeseh (Galen Medical Journal, 2021)
Background: Saffron is traditionally suggested for wound healing in Persian medicine. It is investigated for wound healing effect in multiple studies with promising results. It is not examined that which ingredient of saffron contributes more to this effect. This study was aimed to evaluate and compare the wound healing potential of saffron and its active constituents, crocin, and safranal, in rats. Materials and Methods: Forty female adult rats with induced excision wounds were randomly divided into four groups to receive topical formulation of saffron, crocin, safranal, and placebo for seven days. The Wound area and histopathologic stage of wound healing were evaluated as outcome measures. Results: The wound area was significantly lower in treatment groups (saffron, crocin, and safranal) compared to the control group on day 7 of the intervention. Compared to the control group, the wound in all treated groups showed a decreased inflammatory response and more progression to the proliferation phase. The saffron group showed more advanced healing phase with complete epithelialization of the wound on day 7 of study when partial and no epithelialization was observed in safranal and crocin groups. Conclusion: The study showed the wound healing properties of both safranal and crocin with the slight superiority of safranal. However, saffron seems to be more potent in wound healing effect compared to safranal and crocin as its main active constituents. [GMJ.2021;10:e1900]